Applying P-Diagram in product development process: an approach towards design for Six Sigma - Olalere, Folasayo Enoch; Ab. Aziz Shuaib; Abu Hassan bin Hasbullah (2015)
Successful business enterprises are to a great extent determined by strong sales and overall low operational cost; as a result, improving quality and reducing cost have been one of the important tasks for any business enterprise. These will help in achieving high quality products at reasonable price. Thus, due to the effectiveness of Six Sigma in improving quality and reducing cost, it has become an excellent initiative that is gaining momentum in the business world. However, academics have conducted little research regarding this phenomenon, especially on it applicability in manufacturing industries. Therefore, this paper seeks the knowledge regarding how P-Diagram Model (Taguchi Method) can be applied in product development stage to achieve Design for Six Sigma (DFSS). The paper illuminates on “Process” as the basic unit for Six Sigma and how production process can be enhanced using P-diagram. Following this understanding, the paper demonstrates how P-diagram can be applied in conceptualizing and developing product ideas that put into consideration users intent (User-centred design), reduce variations and thus, lower the risk of product failing.